Cypringlea (Cyperaceae) revisited, a new combination and status - Reznicek, Anton A.; González Elizondo, M. Socorro (Instituto de Ecología, A.C., 2008)
Cypringlea (Cyperaceae), a Mexican endemic genus segregated from Scirpus, includes three species.Cypringlea evadens, previously treated as a variety or under synonymy of C. analecta, is raised here to the specific level. It differs in the degree of inflorescence compounding, proportion of spikes that are peduncled, total number of spikes, as well as leaf width and the proportionate length of inflorescence bracts. A key to distinguish the species, as well as descriptions and data on distribution and habitat are given. Cypringlea analecta is newly recorded for Nuevo León, Tamaulipas and Querétaro, C. coahuilensis, previously known only from the type collection in Coahuila, is recorded also from Nuevo León, and C. evadens is newly recorded for Guerrero and Oaxaca.